Esquerdas na américa do sul: Padr\~oes de inserç\~ao internacional e constrangimentos aos programas de proteç\~ao social - Daniel Ricardo Castelan (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The work analyzes the effects of the pattern of economic internationalization of South America on political coalitions providing support to the social protection programs of the Left parties elected between 1999 and 2010. To achieve the goal, we used hypotheses of political economy built in Europe between the 1970s and 1980s, when structural reforms redefined the basic underpinnings of the social democrat parties and changed the economic and social conditions that supported the Welfare State. Throughout the work, the European countries with similar patterns of international economic integration were used as comparison for the countries of South America.
Keywords: F68; 330; international trade; political economy; South America; political parties